Antigenic conservation of the 15,000-dalton outer membrane lipoprotein PCP of Haemophilus influenzae and biologic activity of anti-PCP antisera. - Deich, R A (1990)
A gene from Haemophilus influenzae encoding an outer membrane lipoprotein of about 15,000 daltons and which comigrates with the peptidoglycan-associated lipoprotein (PAL) of H. influenzae on sodium dodecyl sulfate-polyacrylamide gel electrophoresis has been previously reported and designated pcp gene, and its product has been designated PCP. in order to obtain specific immunologic probes for the analysis of PCP expression, cellular location, and antigenic conservation in H. influenzae, pcp was fused to the lac polylinker region of plasmid pUC19 and the hybrid gene was expressed in Escherichia coli. PCP purified from these cells was used to generate rabbit and mouse polyclonal antisera and mouse monoclonal antibody against PCP. Western immunoblot analysis with anti-PCP monoclonal antibody demonstrated that PCP is present and antigenically conserved in 30 tested strains of H. influenzae, including 27 clinical nontypeable strains. Polyclonal antiserum against PCP killed 9 of 11 clinical H. influenzae strains in a complement-mediated bactericidal assay, and bactericidal activity was additive with bactericidal activity of antisera against PAL. These results indicate that PCP is a potentially valuable component for a subunit vaccine against nontypeable H. influenzae disease, especially in combination with PAL or other components.